Evaluation of land use and occupation in the Ribeirão Graipu sub-basin (MG): A proposal for the conservation of permanent protection areas (APP's) (Research, Society and Development, 2023)
Anthropogenic activities such as the use and occupation of the soil irregularly and without prior planning, have been altering the quality and characteristics of the water, leading to the contamination of aquatic ecosystems. As a result, numerous disturbances occur in freshwater ecosystems, modifying the composition, abundance and diversity of the biota, which makes it imperative to apply an integrated management that limits the impacts of multiple uses of watersheds and their respective tributaries. The objective of this work is to present an evaluation of land use and occupation using the years 2000 and 2020 as a reference, in the sub-basin of the Graipu stream belonging to the municipality of Guanhães, mesoregion of Vale do Rio Doce (Minas Gerais / Brazil). To make the maps, the Geographic Information System (GIS) was used, through the geographic information system QGis version 3.22.1. The years 2000 (initial milestone of the water crisis) and 2020 were used as reference, based on the collection 6 of Coverage and Land Use of MapBiomas. The present study pointed out that there was a subtle growth of urban areas, forestry, forest formation and mosaic of agriculture and pasture in relation to the other areas. In addition, there was a reduction in land use for pasture purposes. In conclusion, it can be inferred that the results found may be related to the creation and implementation of public policies and the increase in discussions on the subject. It is also important to carry out environmental education work considering methodologies for protection and techniques for restoration and conservation of areas, promoting awareness activities, in addition to valuing ecological goods and services.